Financial accounting : international financial reporting standards - Harrison, Walter Jr. T.; Horngren, Charles T.;Horngren, Charles T.;Thomas, C. William (Indianapolis, Indiana : Pearson Education, 2010)
Financial Accounting gives readers a solid foundation in the fundamentals of accounting and the basics of financial statements, and then builds upon that foundation to offer more advanced and challenging concepts and problems.
1. Conceptual framework and financial statements -- 2. Transaction analysis -- 3. Accrual accounting & income -- 4. Internal control & cash -- 5. Short-term investments & receivables -- 6. Inventory & cost of goods sold -- 7. PPE & intangibles -- 8. Liabilities -- 9. Shareholder's equity -- 10. Long-term investments & international operations -- 11. The income statement & the statement of changes in equity -- 12. The statement of cash flows -- 13. Financial statement analysis
Includes index.
Keywords: FINANCIAL ACCOUNTING